Detection of Ehrlichia ruminantium infection in cattle in Cameroon - Seraphine N. Esemu; Roland N. Ndip; Lucy M. Ndip (BMC Research Notes, 2018)
Abstract Objectives Ehrlichia ruminantium infection (heartwater) is a major constraint that impacts negatively on the cattle industry development in sub-Saharan Africa and so far, little is known of the presence of heartwater in cattle in Cameroon. This study sought to investigate the prevalence of E. ruminantium infection in cattle in Cameroon and to determine the predictors of infection. Results A species-specific semi-nested pCS20 polymerase chain reaction was used to screen the buffy coats from 182 cattle (comprising 82 cattle that received intensive tick control regimen and 100 cattle on strategic tick control) from two study sites in Cameroon for E. ruminantium DNA in a cross-sectional study. E. ruminantium infection was confirmed in 12 (6.6%) of the 182 cattle comprising 11 that received intensive tick control and one on strategic tick control. Of the 12 cattle detected, 11 were apparently healthy and one was clinically diagnosed of heartwater. All DNA sequences of pCS20 amplicons were identical to each other (a representative sequence deposited in GenBank under accession number JQ039939). These findings which have veterinary and epidemiological significance, suggest the need for further investigation to determine the extent and role of heartwater in cattle in Cameroon.